Long distance movement of an Arabidopsis Translationally Controlled Tumor Protein (AtTCTP2) mRNA and protein in tobacco - Toscano-Morales, Roberto; Xoconostle-Cázares, Beatriz; Martínez-Navarro, Angélica C.; Ruiz-Medrano, Roberto (Frontiers in Plant Science, 2014)
TCTP (Translationally Controlled Tumor Protein) is an almost ubiquitous protein found in eukaryotes, fundamental for the regulation of development and general growth. The multiple functions of TCTP have been inferred from its involvement in several cell pathways, but the specific function of TCTP is still not known in detail. On the other hand, TCTP seems to respond to a plethora of external signals, and appears to be regulated at the transcriptional and/or translational levels by mechanisms yet to be determined. In the present work, we analyzed the capacity of AtTCTP2 gene products (mRNA and protein) to translocate long distance through tobacco heterografts (Transgenic/WT and WT/Transgenic). The results indicate that both AtTCTP2 mRNA and protein are capable of moving long distance in both directions (stock-scion and scion-stock) with a tendency for movement from source to sink tissue (stock to scion). Interestingly, aerial roots emerged only in heterografts where the protein was detected in both stock and scion, suggesting a correlation between the presence of AtTCTP2 and appearance of aerial adventitious roots. More detailed analysis showed that these adventitious aerial roots harbored the transgene and expressed both transcript and protein. In addition, the protein localization pattern in transgenic aerial and primary roots was basically the same, indicating specific nuclear destination in roots, but also in leaves. These findings provide an approach to understand the role of long-distance movement in the function of plant TCTPs, supporting the notion that some of these act in a non-cell autonomous manner, as the human counterpart, the Histamine Releasing Factor (HRF).